Information System for Batik Profession Certification Institution - Febiharsa, Dhega; Sudana, I Made; Hudallah, Noor (Universitas Negeri Semarang, 2018)
Professional Certification Institution (LSP) as an organ or body that organizes professional trials. Implementation of web-based information systems (online) Professional certification institutions assist management in organizing data, scheduling, detecting assessors' expiration, and providing information to LSP assessors. The purpose of this study is to build an information system for Professional Certification Institutions to facilitate the Batik LSP process also helps in getting faster and more accurate data from the process. The method used in this research is research and development (research and development) with the 4D model, namely Define, Design, Develop, and Dissemination. In the initial stage